Reflections on the Experience of Teaching about Christianity to Jewish Teenagers - Wolff, Judith E. (Studies in Christian-Jewish Relations, 2011)
This reflection-on-action essay shares and analyzes the author's experience of teaching about Christianity to Jewish teenagers.